2017
DOI: 10.11646/phytotaxa.331.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy and micromorphology of the endemic Gypsophila osmangaziensis (Caryophyllaceae) and taxonomic contributions for the genus Gypsophila

Abstract: Gypsophila osmangaziensis, an endemic species from Eskişehir (Turkey) is here studied from the anatomical and micromorphological points of view for the first time. Root, stem and leaf cross-sections as well as seed, leaf and pollen grains surfaces are investigated. Root shows perennial characteristics. Pericycle layer of the stem is composed of sclerenchymatic cells that have 15–17 very thick, layered cell walls. Leaf mesophyll is isobilateral and partly carries druse crystals. Seed surface has an obtuse tuber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
2
1
0
Order By: Relevance
“…Anatomy of root, stem and leaves well fit with the descriptions of Metcalfe & Chalk (1957), Barkoudah (1962) and Ataşlar & Ocak (2017) perfoliata L. was x=17, 18, 24, and 34 (Rice et al 2014).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Anatomy of root, stem and leaves well fit with the descriptions of Metcalfe & Chalk (1957), Barkoudah (1962) and Ataşlar & Ocak (2017) perfoliata L. was x=17, 18, 24, and 34 (Rice et al 2014).…”
Section: Discussionsupporting
confidence: 74%
“…Anatomy of root, stem and leaves well fit with the descriptions of Metcalfe & Chalk (1957), Barkoudah (1962) and Ataşlar & Ocak (2017 , 18, 24, and 34 (Rice et al 2014). It could be suggested that there is polyploidy in some species of Gypsophila based on these amounts.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation